The Role of Local Government in Social Protection Programmes: A Case of Social Assistance Grant for Empowerment (Sage) in Uganda. - Mubiru, John Bosco (ResearchGate, 2015)
Social protection has been recognized as a critical element of national development strategies in both developed and developing countries. Uganda have embraced social protection interventions in the recent years as key to achieving inclusive, pro-poor, and equitable development which is evident in its commitments to declarations at regional and international levels. The government has further established and implemented social protection interventions (both contributory and non-contributory schemes). The Ministry of Gender, Labour and Social Development through the Expanding Social Protection (ESP) Programme with financial support from DFID, Irish Aid and UNICEF is piloting two schemes – Senior Citizen Grants (SCG) and Vulnerable Family Grants (VFG) under the SAGE programme. The local governments have been among the key stakeholders in the implementation of the SAGE programme in the 15 pilot districts. They have participated in range of activities including identification, targeting and selection of beneficiaries; sensitization, awareness raising and community mobilizations; managing grievances; coordination; monitoring and reporting as well as providing office space. The participation of the local governments in SAGE has been attributed to some enabling factors that include the trainings; monthly allowances; logistical support; political capital of the programme and the clear mandate on the roles of local governments. However, local governments’ participation in the SAGE programme have encountered a number of challenges such as staffing gaps; reporting challenges; inadequate financial resources and role conflicts. Despite the challenges, SAGE has also impacted on the performance and service delivery of the local governments in the pilot districts In order to strengthen the effectiveness of the local government’s participation and the objectives of the SAGE programme, there is need to create linkages between beneficiaries and other social services; mainstream SAGE in the local government plans and budgets; strengthen the coordination and information sharing and promoting social accountability.